Biologically Induced Cementation for Soil Stabilisation - Bernard Lium, Donovan Mujah Anak (Curtin University, 2019)
Soil bio-cementation via microbially induced calcite precipitation (MICP) process generates calcite in the soil matrix through ureolysis by bacteria. This research has successfully produced effective calcite crystals; relatively larger in size than previously reported ones, and are rhombohedral in shape that favours the strategic spots of soil pore throats for precipitation. These effective calcite crystals bind sand grains together, resulting in an increase in both the strength and stiffness of the otherwise uncemented soil.